Trans-European transport network and crossborder governance - Guasco, Clement (Proceedings from the Annual Transport Conference at Aalborg University, 2013)
This article looks at the implementation of trans-European transport corridors in the EU and the influence it has on governance within EU member-states. It considers the implementation of such a scheme in the context of cross-border cooperation and discusses the system of governance necessary for coordinating knowledge, efforts and solutions across several national systems. In order to understand this governance setting, one needs to understand the specific quality of transnational governance in the EU, which is neither purely international nor federally integrated. The transport corridor between Malmö and Hamburg is taken as a case for discussion. Cross-border governance is analyzed within a multi-level policy network approach including actors from supranational, national and subnational levels, in order to determine the existence of a policy network across the borders. The main finding is a depiction of the actual state of integration of the crossborder networks related to a green corridor strategy and its implications for the region.